A comparative study of conventional and high-efficiency induction machines using finite-element analysis and equivalent-circuit analysis; PowerTech 2015 - Belyaev N. A. Nikolay Aleksandrovich; Khrushchev Yu. V. Yuri Vasilievich; Svechkarev S. V. Sergey Vladimirovich; Prokhorov A. V. Anton Viktorovich; Wang L. (2015, 2015)
Title screen